Pengaruh Manajemen Laba Terhadap Nilai Perusahaan Rentang Waktu 2019-2023 - Meesy Anugrah Putri; Melda Anjelia; Kharismha Fresty; Agum Murtaib; Siti Rodiah (International Forum of Researchers and Lecturers, 2025)
This article presents an overview of the latest research results discussing the impact of earnings management practices on company value during the 2019-2023 period. This research aims to explore the relationship between earnings management and company value from various perspectives, using qualitative research methods and a case study approach. The researchers searched, analyzed and developed data from previous research, then adapted it to current conditions. The research findings outline the influence of earnings management on company value in the 2019-2023 time period. The research results highlight several trends, including an increased focus on transparency, accountability, as well as the impact of technology on earnings management practices and assessing corporate value. In conclusion, recent research trends show a shift towards deeper and more relevant understanding, with an emphasis on transparency, accountability, the influence of technology, as well as research based on specific industries and country contexts.